Thalidomide Embryopathy Swedish Study: 1987 - 2009 - Thalidomide Embyopathy Swedish Study: 1987 - 2009 - Sjögreen, Lotta; Strömland, Kerstin (University of Gothenburg, 2021)
Since the end of the 1980s a number of studies have been performed at the University of Gothenburg of individuals born in Sweden with birth defects caused by Neurosedyn (Thalidomide Embryopathy - TE). Two pediatric ophthalmologists Kerstin Strömland at the University of Gothenburg, Sweden and Marilyn Miller at the University of Illinois in Chicago USA, performed the initial studies while other researchers have been involved in later studies. We collected data from medical records from their childhood and performed scrutinized examinations of the affected individuals with documentation through photos and videos. These studies of a considerable number of individuals with TE have been recognized as probably being the only of its kind in the world and international researchers have suggested that the data ought to be archived for future studies in teratology.

The first step in this procedure was the Thalidomide Archives Project (TAP) made by Teratology Society (later renamed Society for Birth Defects Research and Prevention). By permission of 16 patients suffering from TE, study data from medical records, examination protocols, photos and videos as well as a Webinar have been archived and made available for members of Teratology Society. It is not permitted or possible to copy any documentation.

The present archived material includes digitized data from two studies of the Swedish population of TE (Neurosedyn).

Study 1 was performed 1987-1989 and consisted of 86 Swedish individuals born with TE and it had a focus on ophthalmology.

Study 2 was performed 2007-2009 by a multidisciplinary team of experts in ophthalmology, speech pathology, orthopedics, dentistry and neuropsychiatry. Thirty-one individuals with TE were examined of whom 25 who had participated in Study 1 are included in this documentation. The data originate from the ophthalmological examinations.

Physical data in the study are archived at the University of Gothenburg, archive number 180:1, Institute of Neuroscience and Physiology, series F4A.

Contents and structure

1. Code list (21-05-21_Code list.xlsx)
Pseudonymized information on case number, sex, information about available documents and about participation in Thalidomide Archives Project (TAP) (in English).

2. Study 1 - Overview of archived material (2021-05-21_TE_Overview.xlsx)
Data on 86 individuals with TE : case number, year of birth, sex, malformation of ears, hearing, facial palsy, Duane syndrome, gaze paresis, tearing when eating and emotionally, primary position of eyes, visual acuity, other eye findings, malformation of thumbs, upper and lower extremities and vertebrae, malformation of heart, lungs, kidneys, anal atresia, other malformations, intellectual disability, autism, combination of defects and number of tablets taken by mother (in English).

3. Study 1 - Anamnestic data (2021-05_21_Study 1_TE History.xlsx)
Data on the mother's pregnancy, intake of Neurosedyn tablets, heredity, early development, schooling, occupation/social, and data on tearing function (in English).

4. Study 1 - Results of eye examination (2021-05-21_Study 1_TE Physical examination.xlsx)
Mostly unpublished data (in English).

5. Study 1 - Results of eye examination (Scanned examination protocols, 123 files, 85 individuals)
Complete data (in English).

6. Study 2 - Results of eye examination (Scanned eye examination protocols, 23 files, 23 individuals)
(in English).

7. Study 2 – Questionnaire answered by participants (Scanned documents, 20 files, 20 individuals)
(in Swedish).

8. Copies of medical records (scanned documents, 82 files, 82 individuals)
Medical reports and certificates from guardians that formed the basis of the decisions for the Board of the Thalidomide Association (Neurosedynskadenämnden) (Swedish text).

9. Study 1 and 2 - Cropped photos (PDF files, 84 files, 84 individuals)
Photos of face, eyes, eye movements, ocular fundus, ears and malformed extremities. The photos are cropped to shelter the identity of the individuals.

10a. Study 1 and 2 - Digitized original photos (jpg-files, individuals 1-86, varying number of files per individual)
Photos of face, eyes, eye movements, ocular fundus, ears and malformed extremities. Photos from Study 1 were scanned from diapositive slides.

10b. Studie 1 - Video recordings (.wmv files and one .mpg file, 21 individuals)
Interviews and documentation of common situations.

Sedan slutet av 1980-talet har ett antal forskningsstudier av de svenskar som fötts med neurosedynskada (talidomidembryopati - TE) genomförts vid Göteborgs universitet. Ansvarig för de ursprungliga studierna var Dr Kerstin Strömland vid Göteborgs universitet, som främst arbetat tillsammans med Dr Marilyn Miller från University of Illinois i Chicago men även med andra forskare. Vi har samlat data från journaler från barndomen och genomfört noggranna undersökningar av de flesta skadade med dokumentering genom foton och videoinspelningar. Det har visat sig att vårt omfattande material av ett stort antal personer med TE är unikt och troligen det enda av sitt slag i världen och internationella forskare av fosterskador har framfört önskemål att det skall bevaras för eventuella framtida studier.

En första arkivering av ett utvalt antal personer med talidomidskada har efter godkännande från de 16 individer som ingår, gjorts vid Teratology Society (numera Society for Birth Defects Research and Prevention) genom Thalidomide Archives Project (TAP) där vi samlat data, foton, videofilmer och sammanställt ett Webinar. Webinariet och övrigt material är endast tillgängligt för medlemmar i Teratology Society och inget material får eller kan kopieras.

Vi har nu sammanställt och skannat forskningsmaterial bestående av undersökningsformulär, journalkopior och intyg från vårdnadshavare samt foton från två undersökningar av personer med neurosedynskada (TE) i Sverige för att arkiveras och göras tillgängligt för framtida forskning.

I Studie 1, som genomfördes 1987–1989, undersöktes 86 personer med talidomidskada av barnögonläkarna Kerstin Strömland, Göteborg och Marilyn Miller, Chicago för att främst studera ögonen hos svenskar med bekräftad TE.

Studie 2 utfördes 2007 - 2009 av ett multidisciplinärt team bestående av ögonläkare, logoped, ortopeder, tandläkare och neuropsykiater. I studie 2 undersöktes 31 personer med TE varav 25 personer, som även deltagit i Studie 1, är inkluderade i detta arkiv. Dokumentationen härrör från ögonundersökningarna.

Fysiskt material i studien, som de digitaliserade data bygger på, finns arkiverade på Göteborgs universitet, och förekommer förtecknade under arkivnr. 180:1, institutionen för neurovetenskap och fysiologi, serie F4A.

Innehåll och struktur

1. Kodlista (21-05-21_Code list.xlsx)
Excelfil med pseudonymiserad information om fallnummer, kön, uppgifter om tillgänglig dokumentation samt uppgifter om förekomst i TAP (Thalidomide Archives Project). Engelsk text.

2. Översikt (2021-05-21_TE_Overview.xlsx)
En sammanställning över data från 86 individer med TE bestående av uppgifter om ID-nummer, kön, missbildning av ytteröron, hörsel, facialispares, Duane syndrom, blickpares, tårproduktion vid ätande och emotionellt, ögonens primärposition, synskärpa, andra ögonfynd, missbildningar av tumme, övre och nedre extremiteter, kotor, missbildning av hjärta, lungor, njurar, analatresi, andra missbildningar, intellektuell funktionsnedsättning, autism, kombination av skador samt uppgift från modern om antal intagna Neurosedyntabletter. Engelsk text.

3. Studie 1 - Anamnestiska uppgifter (2021-05_21_Study 1_TE History.xlsx)
Filen innehåller uppgifter om moderns graviditet och intag av Neurosedyntabletter, hereditet, tidig utveckling, skolgång och yrkesval mm samt tårfunktion. Engelsk text.

4. Studie 1 - Resultat från ögonundersökning (2021-05-21_Study 1_TE Physical examination.xlsx)
I första hand opublicerade data. Engelsk text.

5. Studie 1 - Resultat från ögonundersökning (Skannade undersökningsprotokoll, 123 filer, 85 individer)
Engelsk text.

6. Studie 2 - Resultat från ögonundersökning (Skannade protokoll, 23 filer, 23 individer)
Engelsk text.

7. Studie 2 - Frågeformulär besvarat av deltagarna (Skannade dokument, 20 filer, 20 individer)
Svensk text.

8. Journalkopior (Skannade dokument, 82 filer, 82 individer)
Läkarutlåtanden och intyg från vårdnadshavare som utgjort underlag för Neurosedynskade-nämndens beslut. Svensk text.

9. Studie 1 och 2 - Beskurna foton (PDF-filer, 84 filer, 84 individer )
Foton av ansikte, ögon och ögonrörelser, ögonbottnar, öron och skadade extremiteter. Beskurna för att skydda identiteten.

10a. Studie 1 och 2 - Digitaliserade originalfoton (jpg-filer, individ 1-86, varierande antal filer per individ)
Foton av ansikte, ögon, ögonrörelser, ögonbottnar, öron och skadade extremiteter. Foton från Studie 1 är skannade från diabilder.

10b. Studie 1 - Videoinspelningar (.wmv-filer och en .mpg-fil, 21 individer)
Intervjuer och vardagssituationer.
Svenska studier av personer med neurosedynskada: 1987 - 2009
Keywords: Ophthalmology; Oftalmologi; Thalidomide; Talidomid; Prenatal Injuries; Fosterskador; Neurosedyn; Neurosedyn; Medical and Health Sciences; Medicin och hälsovetenskap